SELECTING THE PROPER GENERATOR (International Journal of Engineering Sciences & Management Research, 2018)
The aim of this article is to explore key aspects for a long-lasting and rentable generator. Its motivation comes from the fact that when selecting turbo-generators sets investors and engineers pave much more attention to the turbines details, but generators end up been choice as commodities and as result the whole generation system suffers from availability issues and less return on their investments. This analyse meant to provide insights about key elements to be observed selecting the proper generator, listing aspects that leverage return on investment and reduce total cost of ownership. Technical and commercial equilibrium are assumptions taken as basis for the study and the fundamental question about what are the key elements of a generator specification tried to be answered